La relation d’emploi à l’aune du multi-sociétariat - Jean Cartellier; Cyrille Ferraton; Nathalie Magne; Delphine Vallade (Revue de la Régulation)
Cooperative Societies of Collective Interest (SCICs) introduced multi-stakeholder cooperatives into French law in 2001. This paper is based on an empirical study in the Occitanie region (France) and looks at the implications of multi-stakeholders for employment relationships. Results show that actors try to attenuate the divergences of interest inherent in this relation although they cannot completely erase them. SCICs do question wage subordination. However, tensions remain over employment contracts, the number of hours worked and/or paid, particularly when employees, volunteers, and consumers are brought together at work and as members.